Implementasi P5 pada Kurikulum Merdeka dalam Pembentukan Karakter Religius di SDN 22 Ujung Gurun Kota Padang - Pratama, M. Zaky; Wirdati, Wirdati (MASALIQ, 2024)
This research aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) program and the formation of religious character through this program at SDN 22 Ujung Gurun, Padang City. The background is the implementation of the Independent Curriculum with one of its contents, namely P5, which aims to shape the character of students in accordance with the values of Pancasila. One of the main characters expected is a religious character. This research is qualitative research with data collection techniques through observation, interviews and distributing questionnaires. The research results show that (1) Implementation of P5 at SDN 22 Ujung Gurun is going well through various programs such as the Religious Harmony Project, Reading the Holy Bible, Religious Local Wisdom, Caring for Others, and Caring for the Environment. (2) These programs have succeeded in forming students' religious character, such as inter-religious tolerance, understanding of religious values, social concern, and responsibility for the environment. Supporting factors for success are human resources, adequate infrastructure, collaboration with parents, and support from residents throughout the school. Meanwhile, the inhibiting factors are teachers' accessibility and understanding of the diversity of learning styles and the lack of learning references.